Concentration-dependent polymorphism of insulin amyloid fibrils - Sakalauskas, Andrius; Ziaunys, Mantas; Smirnovas, Vytautas (PeerJ, 2019)
Protein aggregation into highly structured fibrils has long been associated with several neurodegenerative disorders, such as Alzheimer’s or Parkinson’s disease. Polymorphism of amyloid fibrils increases the complexity of disease mechanisms and may be one of the reasons for the slow progress in drug research. Here we report protein concentration as another factor leading to polymorphism of insulin amyloid fibrils. Moreover, our data suggests that insulin amyloid conformation can self-replicate only via elongation, while seed-induced nucleation will lead to environment-defined conformation of fibrils. As similar observations were already described for a couple of other amyloid proteins, we suggest it to be a generic mechanism for self-replication of different amyloid fibril conformations.
Keywords: Amyloid; Insulin; Polymorphism; Fibril; Protein aggregation